Penerapan Metode Forward Chaining dan Content-Based Filtering pada Sistem Informasi Perawatan Terpadu Pasien Tubercolosis - Putra, Novri Karno Dwi; Samsudin, Samsudin (Program Studi Teknik Informatika Universitas Pamulang, 2024)
Tuberculosis (TB) is a disease caused by infection from the Mycobacterium Tuberculosis bacteria. Treatment for TB patients usually takes a long time and is mostly done independently by the patient. The doctor will usually prescribe anti-tuberculosis drugs (OAT) that are tailored to the patient's condition. While undergoing tuberculosis treatment, patients usually experience symptoms that are usually caused by tuberculosis bacterial infection and also symptoms that arise as a result of consuming OAT. Because the treatment process is carried out independently and the patient will experience many symptoms, the patient will definitely have difficulty carrying out his daily activities. Based on this, the author proposes the design and development of an expert system. This system will use the Forward Chaining method to find the symptoms experienced by the patient, then based on the symptoms found the system will determine side effects and provide suggestions that are relevant to the patient using the Content Based Filtering method. After the system is implemented, it is known that the system can diagnose the side effects of taking OAT from the visible symptoms and can recommend treatment according to the symptoms experienced by the patient.